Baby Bear, Baby Bear, what do you see? - Martin, Bill, 1916-2004.; Carle, Eric (New York : Henry Holt, 2007)
Illustrations and rhyming text portray a young bear searching for its mother and meeting many North American animals along the way.
1 3 6 7 9 11 13 18 20 25 27 29 30 31 39
Keywords: Bears -- Fiction; Mother and child -- Fiction; Animals -- North America -- Fiction; Stories in rhyme